2022
DOI: 10.31083/j.rcm2310350
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Value of Lung Ultrasound Examination in Acute Decompensated Heart Failure Patients with Various Left Ventricular Ejection Fraction

Abstract: Acute decompensated heart failure (ADHF) is one of the most common causes of hospital admission for cardiovascular diseases. ADHF often affects the elderly population, is associated with high morbidity, admission rate and mortality. Pulmonary congestion (PC) is the most common cause of hospitalization among ADHF patients. Previous studies have shown that lung ultrasound (LUS) serves as a valuable tool for the evaluation of PC in patients with heart failure in terms of diagnosis, guiding of the treatment, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Lung ultrasound (LUS) is a helpful tool to detect pulmonary congestion and can be used to guide the diagnosis, treatment and to define prognosis of acute or chronic HF patients with reduced ejection fraction (HFrEF), with preserved ejection fraction (HFpEF) and HFmrEF. [6][7][8][9] The number of LUS detected B-lines (LUS-BL) associated with the severity of pulmonary congestion. Previous single-centre prospective study showed that the number of LUS-BL assessed early during hospitalisation and at discharge was an independent risk factor for adverse in-hospital and after discharge outcomes in acute HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound (LUS) is a helpful tool to detect pulmonary congestion and can be used to guide the diagnosis, treatment and to define prognosis of acute or chronic HF patients with reduced ejection fraction (HFrEF), with preserved ejection fraction (HFpEF) and HFmrEF. [6][7][8][9] The number of LUS detected B-lines (LUS-BL) associated with the severity of pulmonary congestion. Previous single-centre prospective study showed that the number of LUS-BL assessed early during hospitalisation and at discharge was an independent risk factor for adverse in-hospital and after discharge outcomes in acute HF patients.…”
Section: Introductionmentioning
confidence: 99%